Short Video Marketing and Consumer Engagement toward Brand Loyalty among Generation Z - Nurul Haeriyah Ridwan (Journal of Indonesian Management, 2026)
This research investigates how Short Video Marketing (SVM) influences Brand Loyalty (BL) among Indonesian Generation Z consumers, with Consumer Engagement (CE) tested as a mediating factor. Using an explanatory quantitative approach, data were gathered from 250 Generation Z participants chosen through purposive sampling. A five-point Likert questionnaire was administered, and the resulting data were processed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Findings indicate that Short Video Marketing positively and significantly predicts Consumer Engagement (β = 0.685; p < 0.001), and Consumer Engagement in turn significantly shapes Brand Loyalty (β = 0.548; p < 0.001). A direct, positive, and significant link between Short Video Marketing and Brand Loyalty was also confirmed (β = 0.236; p < 0.001), and Consumer Engagement was found to significantly mediate the SVM–Brand Loyalty relationship (β = 0.375; p < 0.001). Overall, the model accounts for 58.4% of the variance in Brand Loyalty (R² = 0.584). Collectively, these results indicate that Consumer Engagement functions as a central pathway through which short-form video content builds brand loyalty, underscoring the value of authentic, creative, and interactive content for reaching Generation Z audiences.